Business Strategy Formulation and Business Model Development of Ewako!shoes (The Indonesian Journal of Business Administration, 2015)
Abstract.Ewako!shoes offer shoes using traditional hand–woven silk from Sengkang as hallmark. This final project purpose is finding appropriate business strategy for ewako!shoes by analyzing internal and external environment which obtained from observation and interview then formulated into EFAS and IFAS calculations. Next, the calculation results are plotted into grand strategy matrix. The results show that ewako!shoes positioned in growth strategy quadrant which has two strategy options, concentration and diversification. After thorough analysis, the most suitable corporate strategy for ewako!shoes is concentration strategy with focus on horizontal integration while the appropriate business strategy is differentiation focus. Finally, the author formulated implementation action plans based on strategy formulation result and development of current business model. Keywords: Business Strategy, Growth Strategy, Concentration Strategy, Business model Development